2011
DOI: 10.1364/ol.36.004173
|View full text |Cite
|
Sign up to set email alerts
|

Proton beam writing of Nd:GGG crystals as new waveguide laser sources

Abstract: Focused proton beam writing has been utilized to fabricate optical channel waveguides in Nd:GGG crystals. The 1 MeV proton beam irradiation creates a local modified region with positive refractive index changes at the end of the proton trajectory, in which the channel waveguide could confine the light field in a symmetric way. Room-temperature laser emission has been achieved at 1063.7 nm, with absorbed pump power of 61 mW (at 808 nm). The obtained slope efficiency of the Nd:GGG waveguide laser system is as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…SRIM (Stopping and Range of Ions in Matter) [16] simulations were performed to calculate depth − distribution of the N + , N 3+ and C 3+ , C 5+ ions in the Er 3+ : TeO 2 − WO 3 glasses and two BGO crystal formulations starting from the energy values used in the experiments. Results obtained for the Er 3+ : TeO 2 − WO 3 glasses shown an increase of the projected range of the N + ions from 1.47 µm to 2.54 µm with a change of the energy MeV from 1.5 to 3.5.…”
Section: Srim Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…SRIM (Stopping and Range of Ions in Matter) [16] simulations were performed to calculate depth − distribution of the N + , N 3+ and C 3+ , C 5+ ions in the Er 3+ : TeO 2 − WO 3 glasses and two BGO crystal formulations starting from the energy values used in the experiments. Results obtained for the Er 3+ : TeO 2 − WO 3 glasses shown an increase of the projected range of the N + ions from 1.47 µm to 2.54 µm with a change of the energy MeV from 1.5 to 3.5.…”
Section: Srim Analysismentioning
confidence: 99%
“…The higher is the N + ion fluence, higher is the refractive index changes in the Er 3+ : TeO 2 − WO 3 glasses. It was observed that the refractive index change saturated at around 6×10 16 ions/cm 2 [20]. Optical characterization was also performed on these channel waveguides.…”
Section: Optical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some controlled micro-modifications occur in the scanning area. Concerning the optical properties, in most of the glasses [30], [33], [34] and some crystals (e.g., Nd:YAG and Nd:GGG) [27], [28], the proton or He + induces an increase of the refractive index in the scanning volume, typically located at the end of the ion track. This feature enables construction of buried waveguides instead of surface ones in some optical materials.…”
Section: Introductionmentioning
confidence: 99%